Late Holocene history of Tokotan Lake (Kuril Archipelago, Russian Far East): The use of lacustrine records for paleoclimatic reconstructions from geologically dynamic settings. (10th July 2020) - Lozhkin, Anatoly; Cherepanova, Marina; Anderson, Patricia; Minyuk, Pavel; Finney, Bruce; Pakhomov, Alexander; Brown, Thomas; Korzun, Julya; Tsigankova, Valeriya
Abstract: A high-resolution, multiproxy analysis of a core from Tokotan Lake, Urup Island, illustrates the complex paleoenvironmental signals that can be preserved in sedimentary deposits from geologically active areas, such as the Kuril Archipelago. Diatom and geochemical analyses of the Tokotan core suggest a shallowing and lessening of the lake area over the last ~3450 cal BP. Without other proxies, the record could be interpreted as showing a general decrease in precipitation over the Late Holocene. However, palynological data indicate no change in vegetation, thereby implying no significant climatic variation. Neither of these paleoclimatic interpretations agrees with Late Holocene reconstructions from the Kuril Archipelago or the Russian mainland. Paleomagnetic data imply variable sediment sources during the lake's history, indicating alterations within the Tokotan catchment (e.g., shifts in gradients or sediment loads in the inflowing streams). Such changes would be particularly important in the Shabalina River, which today has formed a partial dam across the lake's outlet. The results of the Tokotan study indicate that other factors (e.g., volcanism, seismic activity, sea-level changes) rather than climate were more probable determinants of the Late Holocene lake record. Given the geologic dynamism of the region, it is perhaps not surprising that paleo-records from the Kuril Islands display an inconsistency in the numbers and/or duration of proposed Holocene climatic oscillations, underscoring the importance of multiproxy investigations in areas that are or have been geologically dynamic.